Analisis Potensi Bahaya Keselamatan dan Kesehatan Kerja Menggunakan Metode FTA (Fault Tree Analysis) dan TRA (Task Risk Assesment) pada Industri Pandai Besi - Ismail, Aidil; Nofirza, Nofirza; Nur, Muhammad; Nazaruddin, Nazaruddin; Suherman, Suherman (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study is to determine the factors that cause work accidents using the FTA (Fault Tree Analysis) method, identify and assess the risk of other potential work safety hazards using the TRA (Task Risk Assessment) method and design corrective solutions in control measures to reduce the risk of hazards. The results of data processing using FTA show that the main factors causing work accidents are work systems that are not erginomic/unsafe and workers who do not use PPE. While the results of TRA processing obtained that managing the risk of potential work accidents requires the use of PPE so that there is no residual risk. Based on processing with both methods, visual displays at four production stations and Standard Operational Procedure (SOP) on the production floor are designed which are expected to control potential hazards and become a solution so that in the future there will be no more work accidents on the production floor of Blacksmith Sandi